General Description of Glucose and pH in the Urine of Diabetic Mellitus Patients by using Urine Analyzer - Permata, Indra; Rasyid, Nur Qadri; Nurhidayat; Wahyuni, Sri; Muawanah (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
Diabetes Mellitus is a chronic disease that occurs due to the failure of the pancreas to produce enough insulin or the body cannot effectively use the insulin produced. One of the complications of diabetes is diabetic ketoacidosis. KAD is an acute complication of Diabetes Mellitus characterized by increased glucose levels. Diabetic Mellitus has higher levels of calcium stones, and uric acid, therefore the pH of the urine of people with Diabetic Mellitus tends to be more acidic. The purpose of the study was to find out the picture of the results of glucose and pH tests in patients with Diabetes Mellitus. The type of research used in this study is laboratory observation. The sampling technique in this study is random sampling. The number of samples in this study was 10 samples, with the Urine Analyzer examination method. The results of the study showed that out of 10 samples studied, 4 samples were found to be glucose-positive, with a pH range of 5 – 7 and 6 samples were not found to be glucose positive with a pH range of 5 - 6.